Secondary Metabolites from Acremonium Fungi: Diverse Structures and Bioactivities - Tian J, Lai D; Zhou L
Acremonium fungi have been isolated from various sources, such as soil, plants, and marine organisms. The species in Acremonium have been proved to be rich sources of novel and bioactive secondary metabolites. Up to now, 317 metabolites belonging to steroids, terpenoids, meroterpenoids, polyketides, alkaloids, peptides, and miscellaneous have been isolated from Acremonium fungi. These metabolites displayed a wide range of biological activities including antimicrobial, cytotoxic, insecticidal, phytotoxic, antitumor, immunosuppressive, sphingomyelinase inhibitory, antioxidant, anti-inflammatory, antimalarial, and tremorgenic activities. This review highlights the structures and bioactivities of the secondary metabolites from Acremonium fungi reported until October 2014.
Keywords: ACROMONIUM FUNGI; BIOACTIVITIES; SECONDARY METABOLITES